2022
DOI: 10.1039/d2ta00167e
|View full text |Cite
|
Sign up to set email alerts
|

A chemical lithiation induced Li4.4Sn lithiophilic layer for anode-free lithium metal batteries

Abstract: For any battery system involving lithium containing cathode, the anode-free lithium metal battery (AFLMB) exhibits the highest potential energy density. However, the lack of excess lithium amplifies the problems of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 44 publications
(48 reference statements)
2
16
0
Order By: Relevance
“…The second step is lithium nucleation. The current transient curves of LS001 and LB001 are similar to the theoretical curve of transient nucleation [ 35 , 51 ] ( Figure 1 b), wherein the electrode potential decreases to the nucleation potential, instantly forming lithium nuclei on the Cu surface. Finally, the potential rises and enters the growth process.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The second step is lithium nucleation. The current transient curves of LS001 and LB001 are similar to the theoretical curve of transient nucleation [ 35 , 51 ] ( Figure 1 b), wherein the electrode potential decreases to the nucleation potential, instantly forming lithium nuclei on the Cu surface. Finally, the potential rises and enters the growth process.…”
Section: Resultssupporting
confidence: 64%
“…However, many powerful and advanced characterization instruments cannot be directly used to observe in situ the lithium deposition in liquid electrolytes, due to the existence of liquid electrolytes. Many previous studies were carried out by depositing a certain amount of lithium on a substrate, drying it, and transferring it to the characterization instrument [ 34 , 35 , 36 , 37 ]. Based on this research method, lithium deposition is roughly divided into three regions according to the current density.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Li 4.4 Sn layer, which is lithophilic, was also conducive to rapid electrochemical kinetics, resulting in a greater nucleation density, which is conducive to Li ion epitaxy and dense deposition. Zhang et al 75 produced an Li 4.4 Sn coating layer on Cu foil (Li 4.4 Sn@Cu) via a chemical pre-lithiation process. The chemical prelithiation process in the liquid phase promoted the homogeneity and simplicity of the reaction.…”
Section: Promotion Strategies and Failure Analysis Of Aflpbsmentioning
confidence: 99%
“…C, Sn, and Si can form an alloy with Li metal but cannot be soluble in Li metal, resulting in a nucleation overpotential of ˜15 mV at the same current density. In this context, researchers have attempted to modify Cu CCs by introducing lithiophilic elements such as Au, [89] Ag, [90,91,92,93,94] Sn, [47,95,96] Zn, [97] SiO x , [58] Te, [98] and GaInSn [99] to enhance the electrochemical performance and Li plating morphology of AFLMBs. Lin et al reported an epitaxially-induced plating current collector (E-Cu) by coating Cu CCs with a liquid metal (Ga: In: Sn = 68.5:31.5:10).…”
Section: The Significance Of Current Collector Modificationmentioning
confidence: 99%